Moral Values as Material for Teaching Character Education in Up and Doctor Strange Films - Titi Purnama Sari (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2018)
The objectives of this research are to find out moral values in Up and Doctor Strange film that can be used as material for teaching character education that involve in curriculum. This research is a qualitative research through content analysis method. The data in this research was collected through documentation and key informant with expert. In analyzing the data, the researcher used character table by Bohlin’s theory (2013) that consists of moral starting point, 1st morally pivotal point, 2nd morally pivotal point, challenge point, and new change. The result of this research showed there are some moral values in Up and Doctor Strange film that can be used as material for teaching character education involve in curriculum. The moral values are responsibility, caring other people, work hard, appreciate achievement of other people, curiosity, like to read and caring environment. These moral values also include in 18 that should be taught by teacher in teaching character education.